Psychological Alienation And Its Relationship To Decision-Making In A Sample Of The Students Of The Faculty Of Education And Science At The University Of Damascus - Ahmad, Kaerea (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of this research is to uncover the relationship between psychological alienation and decision-making among a sample of last year students at the Faculty of Education and Science at Damascus University. It also aims to identify the differences between the last year students in the Faculty of Education and Science at Damascus University in psychological alienation and decision- (307) students of the last year at the Faculty of Education and Science at Damascus University, divided into (126) psychology and (181) physics, were selected In a random and stratified manner from the Faculty of Education and Science at the University of Damascus Matter of psychological alienation from the preparation of Lina on a scale (2007) and the scale of the decision of the preparation of Yusuf Abdoun (1979), after the Pttbaiqama on a reconnaissance sample confirmed Sedkhma and Thbathma. The results of the research indicated that: - Existence of psychological alienation and the ability to make decisions among the members of the research sample to a medium degree. -There was a statistically significant correlation between psychological alienation and decision-making among the members of the research sample and the correlation value was (0.74(. -There is no difference D statistically in psychological alienation according to the specialization of psychology and physics. - There is no difference in statistical decision making according to the specialization of psychology and physics. - There is a statistically significant difference in psychological alienation according to sex "male and female" in favor of males. - There is a statistically significant difference in decision-making according to gender and male gender.